GluN2D-containing NMDA receptors-mediate synaptic currents in hippocampal interneurons and pyramidal cells in juvenile mice - Engelhardt, Jakob von; Bocklisch, Christina; Tönges, Lars; Herb, Anne; Mishina, Masayoshi; Monyer, Hannah (Frontiers in cellular neuroscience, 2015)
The differential regulation of the two major N-methyl-D-aspartate receptor (NMDAR) subunits GluN2A and GluN2B during development in forebrain pyramidal cells has been thoroughly investigated. In contrast, much less is known about the role of GluN2D, which is expressed at low levels and is downregulated following the second postnatal week. However, it appears that few cells, presumably interneurons, continue to express GluN2D also in juvenile mice. To investigate which hippocampal cell types express this subunit, we generated transgenic mice with EGFP-tagged GluN2D receptors. The expression of the transgene was confined to hippocampal interneurons, most of which were parvalbumin- and/or somatostatin-positive. Electrophysiological and morphological analyses showed that GluN2D was present mainly in fast spiking basket and axo-axonic cells. Based on pharmacological evidence and electrophysiological analysis of GluN2D knockout mice, we conclude that GluN2D-containing NMDARs mediate synaptic currents in hippocampal interneurons of young and juvenile mice and in CA1 pyramidal neurons of newborn mice.
Gesehen am 25.06.2020